2016
DOI: 10.1021/acsmacrolett.6b00804
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Hyperbranched Polyglycerol at Room Temperature

Abstract: In this work we report on a new method for the cationic polymerization of glycidol by citric acid at ambient and solvent free conditions. In this polymerization, citric acid is a proton donor and is able to incorporate in the structure of polyglycerol by reaction with the activated monomer. The molecular weight and degree of branching of the synthesized polymers are affected by the glycidol/citric acid molar ratios and reaction temperature. Due to the citric acid core of the hyperbranched polyglycerols, they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 33 publications
0
37
0
5
Order By: Relevance
“…On the other hand, glycidol is a strained monomer with high reactivity toward ROPs. For example, it can be even polymerized at room temperature by Lewis or Bronsted acids . Therefore, copolymerization of glycidol and γ‐butyrolactone can results in copolymers with high glycerol/ γ‐butyrolactone ratio .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, glycidol is a strained monomer with high reactivity toward ROPs. For example, it can be even polymerized at room temperature by Lewis or Bronsted acids . Therefore, copolymerization of glycidol and γ‐butyrolactone can results in copolymers with high glycerol/ γ‐butyrolactone ratio .…”
Section: Resultsmentioning
confidence: 99%
“…DB of the polymer was 0.43, which was less than hyperbranched polyglycerols synthesized by anionic ROP and close to the DB of polyglycerols synthesized by cationic polymerizations. This could be due to the cationic character of polymerization, which increased L 1,4 units as well as linear oligobutyrolactone fragments in the backbone of polyglycerols . Molecular weight and PDI of the synthesized PGOB was investigated by GPC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Mohammadifar et al, reported the reaction of cationic polymerization at room temperature and solvent free to obtain polyglycerol, the polymerization is classified as green polymerization, in this type of polymerization, citric acid participates as a donor of proton, promoting polymerization, it was reported that this type of polymerization does not require a purification process which indicates that the process is very sustainable, these types of polymers may be potential candidates for biomedical applications [62].…”
Section: Polymermentioning
confidence: 99%
“…Hydroxy-terminated hyperbranched polyether (HTHP) is a novel polymeric material, containing a large number of terminal hydroxyl groups [35,36,37]. Due to its excellent biocompatibility, HTHP is widely employed in biological materials, adhesives, etc.…”
Section: Introductionmentioning
confidence: 99%